High Quality Factor Using Nested Complementary Split Ring Resonator For Dielectric Properties Of Solids Sample - Zakaria, Zahriladha; Abd Rahman, Norhanani; Al-Ahnomi, Rammah Ali Hussien; Al-Hegazi, Ammar Abdullah Hussein; Abd Rahim, Rosemizi; Meor Said, Maizatul Alice; Mohd Bahar, Amyrul Azuan (Applied Computational Electromagnetics Society (ACES), 2020)
A Nested complementary split ring resonator (CSRR) was proposed based on planar structure. The main objective of this work is to get a higher quality factor (Q-factor) with minimal error detection of complex permittivity. The sensor operated at the 3.37GHz resonant frequency and simulated by ANSYS HFSS software. Subsequently, the designed sensor has been fabricated and tested with the presence of several material under test (MUTs) placed over the sensor. The result achieved high unloaded Q-factor, 464. There has been proof of good agreement concerning the results between theoretical, simulation, and measured parameters of error detection, which is below 13.2% real part permittivity and 2.3% the loss tangent. The proposed sensor is practically useful for the food industry, bio-sensing, and pharmacy industry applications.